3D-printed scaffold harboring copper ions combined with near-infrared irradiation for local therapy of cancer - Hao Wei; Dong Chen; Bin Han; Peng Li; Hao Jia; Lizhang Zhu; Hao Yang; Deren Lan; Wei Wei; Haibo Chen; Yongxiang Luo; Yongsheng Zhao (iScience, 2023)
Summary: Cancer is a major health threat and a leading cause of human death worldwide. Surgical resection is the primary treatment for most cancers; however, some patients develop locoregional recurrence. Here, we developed an in situ cancer therapeutic system aimed to locally treat cancer and prevent postoperative recurrence. A functional scaffold, based on alginate/gelatin and crosslinked with copper ions, was fabricated by 3D printing and showed an excellent photothermal effect under near-infrared (NIR) irradiation. The combination of copper ions and NIR effectively killed thyroid cancer cells and patient-derived organoids, indicating a synergetic and broad-spectrum antitumor effect on thyroid cancer through the chemo-photothermal therapy. This implantable stent is designed to provide effective treatment in the vicinity of the tumor site and can be degraded without secondary surgery. The copper-loaded hydrogel scaffold may be a potential candidate for local cancer treatment and pave the way for precise and effective cancer therapy.